Effect of salinity on gene expression, morphological and biochemical characteristics of stevia rebaudiana Bertoni under in vitro conditions - Fallah, F.; Nokhasi, F.; Ghaheri, M.; Kahrizi, D.; Beheshti Ale Agha, A.; Ghorbani, T.; Kazemi, E.; Ansarypour, Z. (Cellular and Molecular Biology, 2017)
Stevia rebaudiana Bertoni is a famous medicinal plant for its low calorific value compounds which are named steviol glycosides (SGs) and they are 150-300 times sweeter than sugar. Among various SGs, stevioside and rebaudioside A considered to be the main sweetening compounds. Soil salinity is one of the most essential stress in the world. Salinity affects the survival and yield of crops. In current study the effects of salinity and osmotic stress caused by different concentration of NaCl (0, 20, 40, 60 and 80 mM) on morphological traits, genes expressionand amount of both stevioside and rebaudioside Aunder in vitro conditions has been investigated. The morphological traits such as bud numbers, root numbers, shoot length (after 15 and 30 days) were evaluated. With increasing salinity, the values of all studied morphological traits decreased. To investigation of UGT74G1 and UGT76G1 genes expression that are involved in the synthesis of SGs, RT-PCR was done and there were significant differences between all media. The highest expression of both genes was observed in plantlets grown on MS media (with NaCl-free). Also, the lowest amounts of gene expression of the both genes were seen in MS+ 60 mM NaCl. Based on HPLC results, the highest amount of both stevioside and rebaudioside A were observed in plantlets grown in MS media (with NaCl-free). Finally, it can be concluded that stevia can survive under salt stress, but it has the best performance in the lower salinity.